Microarray-based kinetic colorimetric detection for quantitative multiplex protein phosphorylation analysis - Holenya, Pavlo; Kitanovic, Igor; Heigwer, Florian; Wölfl, Stefan (Proteomics, 2011)
Commonly used colorimetric detection applied to protein microarrays with enzymatic signal amplification leads to non-linear signal production upon increase in analyte concentration, thereby considerably limiting the range and accuracy of quantitative readout interpretation. To extend the detection range, we developed a kinetic colorimetric detection protocol for the analysis of ELISA microarrays designed to measure multiple phosphorylated proteins using the platforms ArrayTube™ and ArrayStrip™. With our novel quantification approach, microarrays were calibrated over a broad concentration range spanning four orders of magnitude of analyte concentration with picomolar threshold. We used this design for the simultaneous quantitative measurement of 15 phosphorylated proteins on a single chip.